Ecological, Social and Economic Aspects of Italian Marine Spearfishing Tournaments (2009-2020) - Terlizzi, Antonio; Tarantino, Giulio; Sbragaglia, Valerio (Frontiers in Marine Science, 2022)
Marine recreational spearfishing is practiced by a small proportion of recreational fishers and ecological, social and economic aspects of such activities are poorly understood with respect to recreational angling. The Italian Federation of Sport Fishing and Underwater Activities (FIPSAS) started in 2009 the collection of catch data related to Italian spearfishing tournaments. Here, we provide the first snapshot of this catch data regarding 48 tournaments organized in 29 different Italian localities from 2009 to 2020. We also developed a survey to collect social and economic information that has been administrated to participants to the tournaments. We retrieved 8843 specimens caught by spearfishers, which accounted for 33 species and a total biomass of 5665 kg (mean individual mass ± standard error; 0.641 ± 0.008 kg). The five most frequently species represented 78% of the specimens caught (Diplodus sargus 48%; Labrus merula 12%; Sciaena umbra 9%, Labrus viridis 5%; Sarpa salpa 4%). The overall catch per unit effort for all the tournaments was 0.47 ± 0.01 kg/spearfisher/h (mean ± standard error), and we showed interesting effects of type of tournaments and type of displacement on it. We also assessed the accuracy of participants to catch fish in accordance to tournaments-specific minimum weight limits. The five most caught species showed that spearfishers committed errors around 50 g below the weight limit. The survey showed that spearfishers participating to tournaments are big-fish oriented (i.e., they would rather catch one or two big fish than ten smaller fish), but not particularly catch oriented (i.e., they are just as happy if they do not shoot the fish they see and a fishing trip can be successful even if no fish are caught). Regarding the motives for fishing, they fish for experiencing adventure, excitement and new and different things as well as to be underwater. From an economic perspective, the total amount of money that participants spent to participate to the tournaments ranged from 800 to 3500 Euros (mean ± standard deviation; 1800 ± 591 euros). This study represents the first baseline knowledge for an integrative management of contemporary spearfishing tournaments in Italy.